2015
DOI: 10.1002/jbmr.2595
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Multiple Fractures Despite High Adherence to Oral Bisphosphonates: A Binational Population-Based Cohort Study

Abstract: Oral bisphosphonates (BPs) are highly effective in preventing fractures and are recommended first-line therapies for patients with osteoporosis. We identified the incidence and predictors of oral BP treatment failure, defined as the incidence of two or more fractures while on treatment (!2 FWOT) among users with high adherence. Fractures were considered from 6 months after treatment initiation and up to 6 months after discontinuation. Data from computerized records and pharmacy invoices were obtained from Sist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…It is worth keeping in mind that most studies evaluating risk factors looked at general populations, whereas our cohort included only patients currently being treated for osteoporosis. Similar results have also been found by studies that have identified risk factors for treatment failure while on an osteoporosis medication ( 17 , 18 ). Given the significant magnitude of risk found in this study and other for patients who have had a recent fall or fracture, it may be worth considering more intensive therapy for these patients, including possibly using multiple agents when initiating therapy.…”
Section: Discussionsupporting
confidence: 87%
“…It is worth keeping in mind that most studies evaluating risk factors looked at general populations, whereas our cohort included only patients currently being treated for osteoporosis. Similar results have also been found by studies that have identified risk factors for treatment failure while on an osteoporosis medication ( 17 , 18 ). Given the significant magnitude of risk found in this study and other for patients who have had a recent fall or fracture, it may be worth considering more intensive therapy for these patients, including possibly using multiple agents when initiating therapy.…”
Section: Discussionsupporting
confidence: 87%
“…Using routinely collected data with no individual validation of fracture events is another limitation; however, validation of hip and vertebral fracture coding has been carried out previously and has been shown to be accurate. (31) Our definition of second hip fracture is based on previous work (32) and incorporates a 6-month washout from the index fracture to minimize the inclusion of recoding events, although such occurrences cannot be ruled out.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%
“…Extensive research focuses on both understanding the fundamental underlying mechanisms and finding suitable treatments for such patients. However, major health concerns remain, such as secondary drug effects, osteonecrosis of the jaw and atypical femoral fractures 18 19 20 21 , motivating continued search for osteoprotective treatments against bone loss.…”
mentioning
confidence: 99%